2000
DOI: 10.1002/1096-8652(200009)65:1<41::aid-ajh7>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

High rate of TTV infection in multitransfused patients with pediatric malignancy and hematological disorders

Abstract: The prevalence of transfusion-transmitted virus (TTV) infection has not been known in patients suffering from pediatric malignancies and hematological disorders who receive blood transfusion and/or blood products during treatment. Blood samples were taken from 75 patients. TTV infection was identified when TTV DNA was detected in serum by a polymerase chain reaction (PCR) assay. Hepatitis C virus (HCV) and hepatitis G virus (HGV) RNA were also assayed by PCR. TTV DNA was detected in 38 of 75 patients (51%). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…8,9 TTV may also be disseminated by aerosols, since the virus is present in saliva. 8,10 A high rate of TTV infection was found in patients given multiple transfusions 11 and patients with hemophilia. 5,12-14 TTV sequences are frequently detected in clotting factor concentrates prepared from large plasma pools.…”
Section: Introductionsupporting
confidence: 86%
“…8,9 TTV may also be disseminated by aerosols, since the virus is present in saliva. 8,10 A high rate of TTV infection was found in patients given multiple transfusions 11 and patients with hemophilia. 5,12-14 TTV sequences are frequently detected in clotting factor concentrates prepared from large plasma pools.…”
Section: Introductionsupporting
confidence: 86%
“…Similarly, in other reports a higher load of TT Virus genomic DNA was detected in PBMCs of patients with cancer compared with healthy controls ( 41 ). In another study a higher prevalence of TT Virus was found in multi-transfused pediatric patients with malignancies ( 12 , 40 ). Similarly, in this study, a significantly higher frequency of TT Virus molecular infection was found in patients with leukemia compared with controls (42.1% and 12%, respectively).…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, TT Virus infection has been found in 1 - 12% of blood donors reported from different geographical regions. This viral infection was also detected in 18% of patients exposed to blood products and in 4% of patients without parenteral risk factors ( 12 ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…68 The non-enveloped single stranded DNA virus is particularly prevalent in patients with frequent parenteral exposure. 69 Like HGV virus, TTV is efficiently transmitted from mother to child, 70 with long term persistent infection. TTV is commonly associated with hepatitis B (13%), hepatitis C (16%), hepatitis A (5%), and hepatitis E (20%), but there was no correlation between coinfection, TTV titre, and liver damage, suggesting that TTV may not have a pathological role.…”
Section: Transfusion Transmissable Virus (Ttv)mentioning
confidence: 99%